2020
DOI: 10.1039/c9qo01497g
|View full text |Cite
|
Sign up to set email alerts
|

Chelation-assisted transition metal-catalysed C–H chalcogenylations

Abstract: This review summarizes recent advances in C–S and C–Se formations via transition metal-catalyzed C–H functionalization utilizing directing groups to control the site-selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 78 publications
(33 citation statements)
references
References 261 publications
1
32
0
Order By: Relevance
“…Interestingly, the protocol successfully worked on a gram scale. Besides, the reaction also afforded the natural products urolithins (79 a, 79 The merging of visible light photoredox chemistry with iron catalysis constitutes a highly versatile approach to sophisticated organic synthesis. [54] In this context, a visible light-driven lactonization of 2arylbenzoic acids 68 was achieved by Lie and coworkers by employing [Fe(NO 3 ) 3 ] .…”
Section: (E)-cinnamic Acid/2-arylbenzoic Acids/ 2-methyl-11-biaryl As Substratesmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the protocol successfully worked on a gram scale. Besides, the reaction also afforded the natural products urolithins (79 a, 79 The merging of visible light photoredox chemistry with iron catalysis constitutes a highly versatile approach to sophisticated organic synthesis. [54] In this context, a visible light-driven lactonization of 2arylbenzoic acids 68 was achieved by Lie and coworkers by employing [Fe(NO 3 ) 3 ] .…”
Section: (E)-cinnamic Acid/2-arylbenzoic Acids/ 2-methyl-11-biaryl As Substratesmentioning
confidence: 99%
“…They can be used as antitumor, antibacterial, antiproliferative, and antimicrobial active compound. [79] In the regard, in 2018, Wei's group reported a photocatalyst-free, visible light-promoted regioselective selenylation of 4-aminocoumarins 148 under mild reaction conditions (Scheme 43). [80] In this reaction, (NH 2 ) 4 S 2 O 8 and MeCN were used as an oxidant and a solvent respectively.…”
Section: -Aminocoumarins As Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental results showed that aryl trifluoroborates and aryl trihydroxyborate salts were also efficient. By reacting diphenyl diselenide (1 a) with potassium phenyl trifluoroborate (6) or sodium phenyl trihydroxyborate (7) under the identified reaction conditions, the desired product 3 ad was obtained in comparable 90% and 91% yields, respectively.…”
Section: Research Articlementioning
confidence: 99%
“…[6] The versatility and utility of arylchalcogenides motivated chemists to constantly develop different methods for their synthesis. [7] Among them, the formation of aryl-chalcogen bonds based on the oxidative cross-coupling between diorganyl dichalcogenides and arylboronic compounds has attracted considerable attentions. This is attributed to a large degree to the unique features of these two types of reaction partners, including lower toxicity, ready availability, compatibility with wide functional groups, as well as stability towards air and moisture.…”
Section: Introductionmentioning
confidence: 99%